Westonci.ca is the best place to get answers to your questions, provided by a community of experienced and knowledgeable experts. Explore in-depth answers to your questions from a knowledgeable community of experts across different fields. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.
Sagot :
To fill in the equation for this function, let's first identify and define our parameters based on the given answer:
- [tex]\( a = 1 \)[/tex]
- [tex]\( h = 0 \)[/tex]
- [tex]\( k = 0 \)[/tex]
The general form of a cubic function we are considering is:
[tex]\[ y = a(x - h)^3 + k \][/tex]
Plugging in the values we have:
1. Replace [tex]\( a \)[/tex] with 1:
[tex]\[ y = 1(x - h)^3 + k \][/tex]
2. Replace [tex]\( h \)[/tex] with 0:
[tex]\[ y = 1(x - 0)^3 + k \][/tex]
This simplifies to:
[tex]\[ y = x^3 + k \][/tex]
3. Finally, replace [tex]\( k \)[/tex] with 0:
[tex]\[ y = x^3 + 0 \][/tex]
The equation for the function then simplifies further to just:
[tex]\[ y = x^3 \][/tex]
So, the completed equation is:
[tex]\[ y = 1(x - 0)^3 + 0 \][/tex]
In the original template:
[tex]\[ y = [1](x - \underbrace{0}_{\square})^3 + \underbrace{0}_{\square} \][/tex]
Thus, the completed function is:
[tex]\[ y = 1(x - 0)^3 + 0 \][/tex]
- [tex]\( a = 1 \)[/tex]
- [tex]\( h = 0 \)[/tex]
- [tex]\( k = 0 \)[/tex]
The general form of a cubic function we are considering is:
[tex]\[ y = a(x - h)^3 + k \][/tex]
Plugging in the values we have:
1. Replace [tex]\( a \)[/tex] with 1:
[tex]\[ y = 1(x - h)^3 + k \][/tex]
2. Replace [tex]\( h \)[/tex] with 0:
[tex]\[ y = 1(x - 0)^3 + k \][/tex]
This simplifies to:
[tex]\[ y = x^3 + k \][/tex]
3. Finally, replace [tex]\( k \)[/tex] with 0:
[tex]\[ y = x^3 + 0 \][/tex]
The equation for the function then simplifies further to just:
[tex]\[ y = x^3 \][/tex]
So, the completed equation is:
[tex]\[ y = 1(x - 0)^3 + 0 \][/tex]
In the original template:
[tex]\[ y = [1](x - \underbrace{0}_{\square})^3 + \underbrace{0}_{\square} \][/tex]
Thus, the completed function is:
[tex]\[ y = 1(x - 0)^3 + 0 \][/tex]
We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. Thank you for using Westonci.ca. Come back for more in-depth answers to all your queries.